Attraction of Myzus persicae (Hemiptera: Aphididae) to Volatiles Emitted From the Entomopathogenic Fungus Beauveria bassiana. Issue 1 (24th November 2022) - Geedi, Ruchika; Canas, Luis; Reding, Michael E; Ranger, Christopher M
Abstract: Beauveria bassiana (Balsamo) Vuillemin infects a wide variety of insects, including the green peach aphid, Myzus persicae (Sulzer). Volatiles emitted from B. bassiana can act as semiochemical attractants or repellents, with most responses reported to date resulting in insects avoiding B. bassiana . Since insects can detect 'enemy-specific volatile compounds', we hypothesized the preference behavior of M. persicae would be influenced by volatile emissions from B. bassiana . We conducted Petri dish and Y-tube olfactometer bioassays to characterize the preference of M. persicae to B. bassiana strain GHA. During Petri dish bioassays, more apterous and alate M. persicae were recorded in the vicinity of agar colonized by B. bassiana compared to agar, or Fusarium proliferatum (Matsushima) Nirenberg and Ambrosiella grosmanniae Mayers, McNew, & Harrington as representatives of nonentomopathogenic fungi. Petri dish bioassays also determined that apterous and alate M. persicae preferred filter paper saturated with 1 × 10 7, 1 × 10 6, and 1 × 10 5 B. bassiana conidia/ml compared to Tween 80. Y-tube bioassays documented that more apterous and alate M. persicae oriented upwind to volatiles from B. bassiana mycelia compared to agar. Apterous and alate Myzus persicae were also preferentially attracted to 1 × 10 7 and 1 × 10 6 B. bassiana conidia/ml compared to Tween-80 during Y-tube bioassays. These results complement a previous finding that the mosquito Anopheles stephensi (Diptera: Culicidae) Liston is attracted to volatiles from B. bassiana . Future studies aimed at characterizing the olfactory mechanism leading to the attraction of M. persicae to B. bassiana could aid in optimizing lure-and-kill strategies.